2017
DOI: 10.18632/oncotarget.15166
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline directly targets PAR1 to suppress tumor progression

Abstract: Doxycycline have been reported to exert anti-cancer activity and have been assessed as anti-cancer agents in clinical trials. However, the direct targets of doxycycline in cancer cells remain unclear. In this study, we used a chemical proteomics approach to identify the Protease-activated receptor 1 (PAR1) as a specific target of inhibition of doxycycline. Binding assays and single-molecule imaging assays were performed to confirm the inhibition of doxycycline to PAR1. The effect of doxycycline on multi-omics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Furthermore, it has recently been reported that the epithelial status and E-cadherin expression levels mediate cell proliferation in vitro and promotes xenograft growth in vivo [ 35 , 36 ]. The mechanistic link between PAR1 and E-cadherin has been demonstrated in a follow up study where doxycycline was proposed as a novel PAR1 inhibitor and doxycycline treated cells exhibited increased E-cadherin expression and a significantly decreased metastatic potential [ 37 , 38 ]. Considering these findings we might bring an additional explanation for the increased proliferation in shPAR1 tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has recently been reported that the epithelial status and E-cadherin expression levels mediate cell proliferation in vitro and promotes xenograft growth in vivo [ 35 , 36 ]. The mechanistic link between PAR1 and E-cadherin has been demonstrated in a follow up study where doxycycline was proposed as a novel PAR1 inhibitor and doxycycline treated cells exhibited increased E-cadherin expression and a significantly decreased metastatic potential [ 37 , 38 ]. Considering these findings we might bring an additional explanation for the increased proliferation in shPAR1 tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The terminal alkyne-containing GAyne probe was synthetized by linking GA to 2-(3-but-3-ynyl-3H-diazirin-3-yl)-ethanol. The fluorescent group rhodamine-N3 was synthesized in accordance with previously published procedures (25).…”
Section: Synthesis Of Ga Probementioning
confidence: 99%
“…Nevertheless, there is evidence that targeting PAR1 might be a promising treatment strategy. Recently Zhong et al showed that doxycycline is a direct inhibitor of PAR1-thrombin activation, with subsequent down-regulation of tumour cell migration and tumour growth (43). Furthermore Agarwal et al showed inhibition of angiogenesis, ascites formation and metastasis in xenograft models of peritoneal EOC by giving intracellular pepducins to disturb PAR1-MMP signalling systems (37).…”
Section: Discussionmentioning
confidence: 99%